Competitiveness of the Finnish Agriculture after ten years in the EU - K. Tomšík; E. Rosochatecká (Agricultural Economics (AGRICECON), 2007)
Finnish agriculture changed radically with the EU joining in 1995. The commitment of the Common Agricultural Policy (CAP) led to unprecedented changes in economic environment - in agriculture as in processing industry. Finland lost the possibility to regulate the original price level of agricultural products supported by the national border protection and export subsidies. Prices guaranteed by the EU are much lower today than before the EU-membership. Recently, Finland has evaluated ten years being an EU member. Despite its competitive disadvantage, given mostly by unfavourable production conditions, Finnish agriculture has not lost within the competitive environment of the single market and it has tried to take advantage of the opportunities offered by the CAP. The article recapitulates the ten year effort of Finnish agriculture to ensure the competitiveness within the EU single market.